Reklame dan Tata Ruang Kota - Rudi Rohi (Jurnal Inovasi Kebijakan, 2018)
This article focuses on the existence of reclames on major arterial roads related to urban spatial in Kupang City. By using mixed methods based on survey and interview, this study gained a number of interesting findings. The reclames such as billboards, etc, on the major arterial roads in Kupang City are placed without considering the basic aspects of urban spatial planning.The distribution, number, shape, type, size, location, and content of reclamedo not support the aspect of aesthetics, security, order, coziness, and function of zone.On the other hand, the strongly capital interest generated dominant economic function rather than other functions such as social and cultural functions. Instead, there is an extremly indication that the existence of advertisment on major arterial roads even distorted the basic aspects of urban spatial needs and functions.